Preferences of Turkish ENT specialists about academical meetings: a survey study - Cingi, Cemal; Oğhan, Fatih; Akif Abakay, Mehmet; Ulusoy, Seçkin (ENT Updates, 2013)
Objective: The objective of this study was to investigate the current information-seeking behaviors of ENT physicians and ENT trainees in Turkey and their willingness to learn and acquire evidence-based practice skills. Methods: A cross-sectional survey was carried out by distribution of a questionnaire to 740 otolaryngologists employed in Turkey who attended a national otolaryngology meeting in October 2010. Five-hundred forty-three completed questionnaires were gathered. The questionnaire was created as four questions including expectations from academical meetings valuation scoring from one to five points was used to evaluate these four questions in the questionnaire. Results: There was a statistical correlation between the number of years of experience and willingness to acquire information mastery skills. When the responses to the question "Which meetings do you believe that you will benefit mostly?" were analyzed, they preferred to watch surgical operations in international workshops or participate in courses abroad, instead of attending interactive surgical operations or symposiums on a single topic. Based on the responses to the question ’Which meetings or applied courses do you find attractive to participate?" they preferred to attend "courses of cadaver dissection" in lieu of live-interactive surgical operations. Conclusion: Most otolaryngologists in Turkey not only believed that it is essential to acquire specific interactive information from the meetings, but also they were convinced that effective education depends on evidence-based practice with cadavers. Most were willing to increase these information and skills. Results of our article shed light on the points to be considered in educational process of ENT specialists.